1.
Simplifying
"3(2x + 11) = 9"
Reorder the terms:
"3(11 + 2x) = 9"
"(11 * 3 + 2x * 3) = 9"
"(33 + 6x) = 9"
Solving
"33 + 6x = 9"
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-33' to each side of the equation.
"33 +( -33) + 6x = 9 + (-33)"
Combine like terms: "33 + (-33) = 0"
"0 + 6x = 9 +(-33)"
"6x = 9 +( -33)"
Combine like terms: "9 + (-33) = -24"
Divide each side by '6'.
"6x = -24"
Simplifying
"x = -4"
2.
Simplifying
"44 + (-2)(3x + 4) = -18x"
Reorder the terms:
"44 + (-2)(4 + 3x) = -18x"
"44 + (4 *( -2) + 3x *(-2)) = -18x"
"44 + (-8 + (-6x)) = -18x"
Combine like terms: "44 +( -8) = 36"
"36 +( -6)x = -18x"
Solving
"36 +( -6)x = -18x"
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '18x' to each side of the equation.
"36 + (-6)x + 18x = -18x + 18x"
Combine like terms:"-6x + 18x = 12x"
"36 + 12x = -18x + 18x"
Combine like terms: "-18x + 18x = 0"
"36 + 12x = 0"
Add '-36' to each side of the equation.
"36 + (-36) + 12x = 0 +(-36)"
Combine like terms: "36 + (-36) = 0"
"0 + 12x = 0 +(-36)"
"12x = 0 + (-36)"
Combine like terms:"0 + (-36) = -36"
"12x = -36"
Divide each side by '12'.
"x = -3"
Simplifying
"x = -3"
Comments
Leave a comment